Hubungan Antara Preferensi Belajar Terhadap Gangguan Depresi dan Gangguan Cemas Pada Mahasiswa Preklinik Suatu Fakultas Kedokteran - Carissa Faustina; Dharmady Agus (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2017)
Background: Students have different learning preferences in terms of assimilation and processing information. VARK learning preferences, which were introduced by Fleming, can identify learning preferences based on sensory modality. The model categorizes students into four different learning preferences, namely visual, aural, read/write, and kinesthetic. In his book, Westwood stated that the wrong application of learning preferences may lead to depressive disorder and anxiety disorder. Method: This study is a cross sectional study. The study was conducted by interviewing respondents to determine whether they have depressive disorder and anxiety disorder. Respondents will fill up a VARK questionnaire to determine their learning preferences. Samples will be collected from as many as 260 pre-clinical student of faculty of medicine of Atma Jaya Catholic University of Indonesia. Data will be collected and analyzed by using Chi Square test. Results: The result showed that there is no significant relationship between learning preferences and depressive disorder (p = 1,000), as well as anxiety disorder (p=0,477). Conclusion: There is no relationship between learning preferences and depressive disorder, as well as anxiety disorder.